Impact Of Seasonal Variation On Physiological Traits And Biochemical Constituents In Silk Glands Of Bombyx Mori L. (Applied Biological Research, 2015)
The study was conducted during spring and summer seasons of 2010-2011  to examine the changes in biochemical constituents in silk gland contents  and to identify the races with better growth of silk glands in various  seasons. Larval weight and silk gland weight and size were significantly  high in ‘SK-1’ and ‘SK-6’ and low in ‘CSR-2’ during both the seasons. The  values were marginally high in spring than summer season. Biochemical  contents in silk glands decreased more in summer than spring. There was  no substantial variation in the expression of molecular weight of silk gland  proteins in all the genotypes tested. Carbohydrate and protein contents  were significantly high in race ‘SK-1’ during both the seasons but low  values in race ‘CSR-2’. There was no substantial difference in the  molecular weight of silk gland proteins in different breeds evaluated.
Keywords: Bombyx mori; carbohydrates; proteins; seasons; SDS PAGE; silk gland